Power up : taking charge of your financial destiny - Dvorkin, Howard S. (John Wiley & Sons, Inc., 2013)
A proven survival guide for these economically rocky, debt-ridden times Millions of people suffer financial hardship due to job loss and a variety of other factors. What you need to do in order to take control of your financial destiny includes changing the way you confront and deal with everyday pressures related to shopping, advertising, credit cards, keeping up with the Joneses, and spending money. In Power Up, Howard Dvorkin'founder of Consolidated Credit Counseling Services'draws on his years of experience helping thousands of people overcome devastating financial hardship. He provides you with time-tested strategies and powerful tools to rebuild your financial life on a solid and enduring foundation. Besides discussing guidelines for creating a realistic budget and sticking to it, Dvorkin also shares tips on how to learn to live without credit cards'and love doing it'as well as puts you in a better position to understand the difference between what you want and what you need.-Filled with effective budgeting tools, worksheets, and other valuable forms -Provides a look at the tricks that lenders and credit card companies use to make you a slave to debt -Offers ideas on how to redirect your urge to shop into activities that satisfy your deeper needs and methods to improve your fiscal psychology -Contains priceless advice on how to educate your kids about money and personal finance Do you want a chance to start over again with a clean slate' Do you want the peace of mind that comes with knowing you're in charge of your financial destiny' If you answered yes to any of these questions, then it's time to Power Up!